Implementation of islamic story method in instilling akhlak values in elementary school students - Mukarramah, Mukarramah (Educenter : Jurnal Ilmiah Pendidikan, 2023)
The purpose of this study was to determine the application and impact of the Islamic story method in instilling moral values in students as well as the driving and inhibiting factors in the application of the Islamic story method in instilling moral values in students. The type of research used is qualitative research. The data sources in this study were principals and teachers. The research instruments used were observation guidelines, interview guidelines, and documentation. Documentation. The data analysis technique used is data reduction, data presentation, and verification or conclusion drawing. The results showed that the application of the Islamic story method can teach students to emulate and imitate all the praiseworthy actions possessed by Islamic figures, especially the Prophet Muhammad SAW who became a role model. The impact of the Islamic story method in instilling moral values in students at SDN 352 Tobemba Kab. Luwu, The impact of a teacher's success in instilling moral values in students is inseparable from teaching morals which is closely related to the methods or strategies used by the teacher in teaching in his class according to the material presented. This is very influential on the success of teachers in instilling moral values in students.